Leading with(out) sacrifice? A public-goods experiment with a super-additive player - Andreas Glöckner; Bernd Irlenbusch; Sebastian Kube; Andreas Nicklisch; Hans-Theo Normann (Max Planck Institute for Research on Collective Goods, 2009)
We analyse two team settings in which one member in a team has stronger incentives to contribute than the others. If contributions constitute a sacrifice for the strong player, the other team members are more inclined to cooperate than if contributions are strictly dominant for the strong player.
Keywords: C91; C92; H40; H41; 330; Experiments; Leadership; Reciprocity; Voluntary Contribution Mechanism; Gruppenarbeit; Öffentliches Gut; Spieltheorie; Führungspersönlichkeit; Reziprozität; Test